Slowing down in the good old days : the effect of nostalgia on consumer patience - Huang, Irene Xun (2018)
Nostalgia, which is induced by reminiscing about a positive past experience, can counteract loneliness and promote prosocial behavior. However, the process of recalling and thinking about a nostalgic experience can have quite different effects. Because nostalgic experiences rarely reoccur, people are motivated to savor them by prolonging the time they reminisce about them. The tendency to savor these experiences generalizes to situations that participants encounter later, thus increasing consumer patience. For this effect to emerge, however, consumers must be aware that waiting will be beneficial to the attainment of a benefit. Moreover, the relationship between nostalgia and consumer patience is diminished when people perceive a nostalgic experience to be repeatable or when they intensify their memory of the experience rather than prolonging it. Eight studies confirmed these effects and processes that underlie them.